"Let loose in the unthinkable unspeakable": waiting and alterity in Samuel Beckett's trilogy - Marais, Jessica (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2016)
In this thesis, I examine the interrelated roles of waiting and alterity in Samuel Beckett's trilogy of novels: Molloy, Malone Dies and The Unnamable. The conventional understanding of waiting is as an intentional relationship between a waiting subject and an awaited object. This kind of waiting is end-directed, and, in order for it to be worthwhile, the awaited must, at some point, arrive. In the trilogy, however, the awaited never does arrive, and it is my contention that the novels are concerned with an unconventional kind of waiting, which, being without object or end, takes the form of a non-intentional relationship between waiter and awaited. Significantly, through the non-intentional wait, the subject awaits the unawaited. She or he thereby encounters the radically other, or that which cannot be rendered familiar or assimilated in any way "“ an unthinkable, unspeakable, ungraspable excess that overflows the limits of thought and language. The texts foreground the vexed question of response to such alterity: how can one approach the ungraspable as ungraspable, when it is in the nature of any approach to attempt to grasp? I argue that the texts explore a paradoxical form of "incurious seeking" as an avenue to accommodate the absolutely other.
Keywords: Uncatalogued